2022
DOI: 10.1007/s10802-022-00938-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Worry Socialization and Toddler Inhibited Temperament: Transactional Associations and Stability across Time

Abstract: influence their children's behaviors, socioemotional competencies, and psychological adjustment. Increasingly, however, theory (Dadds & Roth, 2001;Sameroff, 2010) and research (Yan et al., 2018) alike have pointed to the variety of ways in which children, in turn, impact the caregiving environment that they receive. Much of this recent research has focused on child temperament as a source of influence. The current study builds upon this foundation and provides an innovative contribution to the child anxiety ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, there was no support for the opposite relation: low parental encouragement at age 2 did not predict the parental perception of child shyness at age 4. Expanding on these findings, Price and Kiel (2022) found that toddlers' dysregulated fear in low‐threat laboratory tasks at age 2 predicted mothers' perception of children's inhibited temperament at age 3, which in turn predicted mothers' non‐supportive responses (i.e. punitive behaviors, minimizing and distress reactions) at age 4.…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 98%
See 1 more Smart Citation
“…However, there was no support for the opposite relation: low parental encouragement at age 2 did not predict the parental perception of child shyness at age 4. Expanding on these findings, Price and Kiel (2022) found that toddlers' dysregulated fear in low‐threat laboratory tasks at age 2 predicted mothers' perception of children's inhibited temperament at age 3, which in turn predicted mothers' non‐supportive responses (i.e. punitive behaviors, minimizing and distress reactions) at age 4.…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 98%
“…Importantly, there is evidence for both child‐to‐parent and parent‐to‐child effects; however, these effects are often not direct but are mediated by other processes, such as parental perception of child behavior (e.g. Price & Kiel, 2022) and/or a specific parenting behavior (e.g. Kiel et al., 2021).…”
Section: The Role Of Caregiving In the Relation Between Behavioral In...mentioning
confidence: 99%